Effect of xylanases on peroxide bleachability of eucalypt (E.globulus) kraft pulp - Shatalov, Anatoly (2013)
Industrial eucalypt (E. globulus L.) kraft pulp was treated with two commercial xylanase preparations Ecopulp® TX-200A and Pulpzyme® HC (endo-1,4- -xylanase activity; EC 3.2.1.8) and bleached by totally chlorine-free (TCF) three-stage hydrogen peroxide bleaching sequence, without oxygen pre-delignification. The effect of enzymatic stage on pulp properties and bleachability has been studied and compared with reference (control) pulps, processed without enzyme addition. The similar mode of enzymatic action was noted for both xylanase preparations. Final brightness of 86% ISO was achieved after complete bleaching. Direct bleaching effect caused pulp brightening (by 1.2–1.5% ISO) and delignification (by 7–10%) immediately after the enzymatic stage. The maximal bleach boosting was shown after the first peroxide stage and then diminished, despite the progressive increase in delignification over the control. The loss in efficiency of xylanase treatment by the end of peroxide bleaching was associated with specific behavior of xylan-derived chromophores, i.e., hexenuronic acids